1990
DOI: 10.3109/17453679008993065
|View full text |Cite
|
Sign up to set email alerts
|

Secondary repair of ulnar nerve injury: 44 cases followed for 2 years

Abstract: A series of 44 patients with complete section of the ulnar nerve was reviewed on average 2 years after secondary repair. The procedures applied were fascicular grafting in 33 cases, epineural suture in 7, and suture in 4. Useful ulnar motor function was restored in 22 cases of fascicular grafting, in all 4 of fascicular suture and in 3 of epineural suture. Sensibility recovered in 23 patients operated on by fascicular grafts and in 10 of 11 treated by epineural or fascicular suture. Cases with unsatisfactory r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 6 publications
2
16
0
Order By: Relevance
“…Of these, 126 were selected for review of the full text after primary screening, and 67 were judged to meet the criteria for inclusion in the present study[78910111213141516171819202122232425262728293031323334353637383940414243444546474849505152535455565758596061626364656667686970717273]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 126 were selected for review of the full text after primary screening, and 67 were judged to meet the criteria for inclusion in the present study[78910111213141516171819202122232425262728293031323334353637383940414243444546474849505152535455565758596061626364656667686970717273]. …”
Section: Resultsmentioning
confidence: 99%
“…Outcomes are poorer when the repair is delayed by more than 1 year because muscle atrophy becomes irreversible at 1.5–2 years after the loss of innervation. Barrios et al[15] suggested that nerve repair should be performed within 3 months of the injury, and that the time from injury to repair should not exceed 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…However, various publications claimed that there seems to be a better sensory recovery outcome if a nerve defect is treated primarily [25, 78]. Apart from that, there is an unfavorable prognosis for waiting more than 6 months or one year after performing a nerve repair [8487]. For example, in some cases of strong contamination, secondary reconstruction is required.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of peripheral nerve injuries depends on various factors such as the patient age, type of injury, severity of trauma, delay between the time of injury and repair, presence of additional organ injury and infection, affected nerve, distance between injury level and the affected organ, status of the anatomical integrity of the injured nerve, length of the defect between the proximal and distal ends and the experience and techniques of the surgeon (3,29,(30)(31)(32). Prognoses are better transection were associated with good recovery, whereas, neuroma-in-continuity or complete irregular transections were related to moderate or poor outcomes (8).…”
Section: █ Discussionmentioning
confidence: 99%